Seasonal variations in some elements of the quality of the Tigris waters between Qaber Abd and al-Qayara - Taha Al-Tayyar; Abdul mohsin Shihab (College of Education for Pure Sciences, 2005)
Surface water is the main source of water in Mosul city. Wastes including liquid and solid is finally reach the surface waters like rivers. As the length of the river increases, the utilization of the river water increases also and therefore the quantity of wastes and pollution increases. This research is conducted on a stretch of Tigris river south Mosul city up to Qayara city, to study the variation in cations like calcium, magnesium, sodium and potassium. In addition, to the total hardness, pH, electrical conductivity and temperature were also recorded in three locnlions along a period of year. The results showed higher concentrations in the studied parameters than Mosul city due to the effect of rainfall, surface soil erosion and surface runoff. Also, there was a clear effect of flood season on ions concentration. In addition, the mixing of Tigris river and Al-Zab river waters contribute in ions concentration variations. The statistical analysis showed a significant variation in ion concentration with time.